2017
DOI: 10.1158/1940-6207.capr-17-0075
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Wheel Running Reduces the Acute Inflammatory Response to Liver Carcinogen in a Sex-specific Manner

Abstract: Inflammation contributes to the development of cancer, yet acute inflammatory responses are also needed to eradicate tumorigenic cells and activate adaptive immune responses to combat cancer. Physical exercise has direct immunomodulatory effects, and in line with this, exercise has been demonstrated to inhibit tumor growth, including diethylnitrosamine-(DEN)-induced hepatocarcinoma. Having observed a sex-dependent development of DEN-induced hepatocarcinoma, we aimed to evaluate the effect of exercise and sex o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Exercise induced suppression of tumour initiation and growth may be mediated by effects on tumour metabolism and immune function. Inflammation is critical in cancer development and VE has been shown to attenuate the inflammatory response in mice following carcinogen exposure, promoting more efficient clearance of damaged cells [14]. Additionally, VE decreases tumour incidence and growth via regulation of key immune cells, including natural killer (NK) and effector lymphocytes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise induced suppression of tumour initiation and growth may be mediated by effects on tumour metabolism and immune function. Inflammation is critical in cancer development and VE has been shown to attenuate the inflammatory response in mice following carcinogen exposure, promoting more efficient clearance of damaged cells [14]. Additionally, VE decreases tumour incidence and growth via regulation of key immune cells, including natural killer (NK) and effector lymphocytes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Running wheel exposure is commonly employed as a voluntary PA model in rodents, since this protocol is uncomplicated, easy, and results in a quantifiable measure of PA ( Sherwin, 1998 ). Although there is no consensus on the ground mechanisms controlling running wheel activity ( Novak et al, 2012 ), use of a running wheel increases the average rodent life expectancy by nearly 10% ( Holloszy, 1998 ); produces antidepressant- and anxiolytic-like effects ( Cunha et al, 2013 ; Mazur et al, 2017 ), which are paralleled to adult neurogenesis and neuronal survival ( van Praag et al, 1999a , van Praag et al, 1999b ); cardioprotection ( Bronikowski et al, 2003 ; Naderi et al, 2015 ); hepatoprotection ( Bay et al, 2017 ; Zolfagharzadeh and Roshan, 2013 ); and skeletal muscle trophism ( Brooks et al, 2018 ; Takigawa et al, 2019 ). Studies have indicated that running wheel exposition exerts its positive effects on health through a variety of biological pathways, but the exact mechanisms underlying its influences on health are not fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…In ammation is critical in cancer development and VE has been shown to attenuate the in ammatory response in mice following carcinogen exposure, promoting more e cient clearance of damaged cells [14]. Additionally, VE decreases tumour incidence and growth via regulation of key immune cells, including natural killer (NK) and effector lymphocytes [13].…”
Section: Introductionmentioning
confidence: 99%